Relação entre a erosão marginal, atributos físicos do solo e variáveis hidrológicas e climáticas no baixo São Francisco sergipano - Rocha, Igor Pinheiro da (2009)
Changes in the hydrological regimen of the Lower São Francisco River, caused by the installation of big hydroelectric plants in the river channel, have provoked an advanced erosion process by the riverbank vulnerability and also to the amplified character of some hydrological and climatic variables in this part of the river basin. The consequence of this fast erosion process is translated in an environmental, economic and social lack of sustainability to the region, which had negative impacts in fish assemblages, navigation, civil construction and reduction of agroecosystem s productive area. The objective of this work was to verify the influence of the soil physical characteristics and the hydrological and climatic variables in the erosion process in the right margin of the Lower São Francisco River. Through labs assays of soil samples, it was possible to know the main soil physical characteristics of the bank slope and establish the relations with the vulnerability to the riverbank erosion. Historical series of hydrological and climatic variables has been investigated in order to verify a correlation between these variables and the erosion rates. The main soil characteristic that contribute to its disaggregation was the soil texture, mainly composed by coarse particles. It was observed that slope is vulnerable to the riverbank erosion, that doesn t possess a necessary particles aggregation, what characterize stability. The regular rain season in the region has a little contribution to the increase of bank erosion. However, this variable influences the wind direction. Also, it was recognized a correlation between the river s discharge increase and water flux velocity, with a remarkable increase of riverbank erosion, what suffers influences from the reorientation of the natural waves front, shocking against the slope.